Learning Based on QR Code Technology to Improve Teacher Performance at SDN 90 SIPATANA (Journal of Pedagogical Inventions and Practices, 2022)
The purpose of this research is to carry out QR Code-based learning to improve teacher performance. In this study using several data collection techniques, namely, interviews, documentation and observation. Interviews were conducted with elementary school teachers at SDN 90 SIPATANA for a preliminary study and to assess the equipment being made. In this study, the results of the study showed that the data was collected through teacher interview observations, then managed the data, and concluded whether the Quick Response Code learning media was used in the teaching and learning process in class VI at SDN 90 SIPATANA. The result of this QR Codebased learning is to increase the effectiveness of the teacher's performance in learning, streamline learning time, add insight, and provide a new atmosphere in learning